BLENDING TECHNOLOGY WITH PEDAGOGY: EVALUATING THE ROLE OF ICT AND MULTIMEDIA TOOLS IN DEVELOPING ENGLISH WRITING PROFICIENCY - N. SIVAKAMI,; Dr.S.GUNASEKARAN, (The Bioscan, 2025)
n the rapidly evolving landscape of education, the integration of Information and Communication Technology (ICT) and multimedia tools has redefined the dynamics of language learning, particularly in the development of writing skills. This study explores the effectiveness of ICT-integrated pedagogical strategies in enhancing English writing proficiency among undergraduate students. Grounded in constructivist and communicative language teaching theories, the research adopts a mixed-methods approach, combining quantitative analysis of writing assessments with qualitative insights from student and teacher interviews. Participants from engineering colleges in Tamil Nadu were exposed to a range of digital tools including interactive writing platforms, online collaborative environments, visual prompts, and audio-visual feedback systems over a semester. The findings reveal a significant improvement in writing coherence, lexical range, syntactic accuracy, and learner engagement. Students reported higher motivation and autonomy in writing tasks when exposed to multimedia-supported instruction. The study also highlights the pedagogical shift from traditional grammar-based instruction to learner-centered, process-oriented writing approaches. Challenges such as digital literacy gaps and access disparities were also noted. The research concludes that the purposeful integration of ICT and multimedia not only enhances writing proficiency but also fosters a more dynamic and inclusive learning environment. The paper offers recommendations for educators and curriculum designers seeking to implement technology-driven writing pedagogy in English language classrooms.